2008
DOI: 10.4314/eamj.v84i3.9513
|View full text |Cite
|
Sign up to set email alerts
|

Fine needle aspiration cytology of thyroid nodules at Kenyatta National Hospital, Nairobi

Abstract: Objective: To determine the pattern of thyroidal nodules diagnosed by (FNA) cytology. Design: A cross-sectional study. Setting: Kenyatta National Hospital (KNH)-a University of Nairobi affiliated hospital. Subjects: Forty two patients seen at FNA clinic at KNH between June and August 2001. Results: The female to male ratio was 7:1, with the majority in the age group 31-50 years. Overall 88.1% patients had benign FNA cytologic diagnostic results, 2.4% had a malignant, and a suspicious result respectively and 7.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 8 publications
(5 reference statements)
2
3
0
Order By: Relevance
“…The female to male (F:M) ratio was 15.5:1 meaning that this is predominantly a disease of women. This was observed in related studies within the East African region 7,12 . In all patients the main presenting complaint was an anterior neck swelling with median time interval to presentation of 364 weeks (7 years) [ Table 2].…”
Section: Discussionsupporting
confidence: 81%
“…The female to male (F:M) ratio was 15.5:1 meaning that this is predominantly a disease of women. This was observed in related studies within the East African region 7,12 . In all patients the main presenting complaint was an anterior neck swelling with median time interval to presentation of 364 weeks (7 years) [ Table 2].…”
Section: Discussionsupporting
confidence: 81%
“…In our study, most of the lesions were observed in females, correlating with studies by CK Sang et al, Gupta R et al, and Rupam et al, have similar findings. 8,9 Most lesions from our study were Benign of Bethesda category-II showing similar findings as Shukla et al 10 11,12 Cytologically, hurthle cells & granulomas (Figure 1) were demonstrated in hashimoto thyroiditis, some of the cases showed multinucleate giant cells.…”
Section: Discussionsupporting
confidence: 86%
“…In one study from Kenya, benign thyroid nodules were accurately distinguished from malignant nodules, while the FNAB was best performed by cytopathologists. The authors of this study recognize, however, that this diagnostic excellence on the part of the cytopathologist requires considerable skill and technical experience 39 . In addition, the FNAB can provide material for ancillary testing of thyroid lesions.…”
Section: Introductionmentioning
confidence: 94%
“…The authors of this study recognize, however, that this diagnostic excellence on the part of the cytopathologist requires considerable skill and technical experience. 39 In addition, the FNAB can provide material for ancillary testing of thyroid lesions. For example, a survey of countries in the Gulf Cooperation Council highlighted that only less than 10% of indeterminate nodules were being sent for molecular testing, however interest for molecular testing for indeterminate thyroid FNAs to supplement diagnosis was much higher.…”
Section: Fnab In Thyroid Nodulesmentioning
confidence: 99%